Beyond the developmental state industrial policy into the twenty-first century - edited by Ben Fine (London Pluto Press, 2013)
Moving beyond abstract economic models and superficial descriptions of the market, Beyond the Developmental State analyses the economic, political and ideological interests which underpin both the state and the market.
Includes bibliographical references (p. 268-296) and index.
Keywords: Industrial policy--Developing countries